Community Perception Of Kuwil City Forest Management, North Minahasa District - Gabriel Manguru; Hengki Djemie Walangitan; Maria Sumakud (Jurnal Agroekoteknologi Terapan, 2023)
The aim of the study was to analyze people's perceptions of the management of the Urban Forest in North Minahasa Kuwil Village and the socioeconomic factors that influence it. Determination of perception concept data in this study was carried out using a quantitative approach with a Likert scale. includes three perceptions, namely cognitive, affective, and psychomotor. Each domain is measured using multiple-choice questions. The results showed that the level of public perception of urban forest management was classified as high to moderate (75%), the results also showed that the level of perception had a relationship with work. For the results of the analysis of socio-economic factors that affect the level of community perception, the socio-economic factors of the Kuwil Village community affect the level of perception of each respondent, because the higher the education and occupation of the respondent also affects the level of perception of the respondent for the views and opinions given from the respondent. Keywords: City Forest, Kuwil Village, Â Â Forest Abstrak Penelitian bertujuan untuk menganalisis persepsi masyarakat terhadap pengelolaan Hutan Kota Desa Kuwil Minahasa Utara serta faktor sosial ekonomi yang mempengaruhinya. Penentuan data konsep pesepsi pada penelitian ini dilakukan dengan menggunakan pendekatan kuantitatif dengan skala Likert. mencakup tiga rana persepsi yaitu kognitif, afektif dan psikomotorik. Masing-masing ranah diukur menggunakan pertanyaan dengan pilihan ganda. Hasil penelitian menunjukan bahwa tingkat persepsi masyarakat terhadap pengelolaan hutan kota tergolong tinggi sampai sedang sebesar (75%), hasil penelitian juga menunjukan bahwa tingkat persepsi memiliki hubungan dengan pekerjaan. Untuk hasil analisis faktor sosial ekonomi yang mempengaruhi tingkat persepsi masyarakat, bahwa faktor sosial ekonomi masyarakat desa kuwil mempengaruhi tingkat persepsi dari setiap responden, karena semakin tinggi pendidikan dan pekerjaan responden juga mempengaruhi tingkat persepsi dari responden untuk pandangan dan pendapat yang diberikan dari responden. Kata kunci: Hutan Kota, Desa Kuwil, Hutan.